2019
DOI: 10.1016/j.str.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Exploration of SDS22 Interactions with Protein Phosphatase PP1 and the Splicing Factor BCLAF1

Abstract: Highlights d The LRRs of SDS22 interact with PP1 helices a5 and a6 d A basic surface patch of SDS22 binds phosphorylated BCLAF1 d Many PP1 holoenzymes contain SDS22 as a third subunit d SDS22 prevents the autodephosphorylation of PP1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 68 publications
5
32
0
Order By: Relevance
“…These data are consistent with our PP1 Y134A SPR data ( Fig. 4D) and previously published PP1 K147A/K150A pull-down data (37) which also show that these variants fail to bind SDS22. Together, these data show that, both in vivo and in vitro, Lys147/ Lys150 and Tyr134 are critical for SDS22 binding.…”
Section: Sds22 and Other Pp1 Regulatory Proteins Prevent Pp1 Aggregatsupporting
confidence: 94%
See 1 more Smart Citation
“…These data are consistent with our PP1 Y134A SPR data ( Fig. 4D) and previously published PP1 K147A/K150A pull-down data (37) which also show that these variants fail to bind SDS22. Together, these data show that, both in vivo and in vitro, Lys147/ Lys150 and Tyr134 are critical for SDS22 binding.…”
Section: Sds22 and Other Pp1 Regulatory Proteins Prevent Pp1 Aggregatsupporting
confidence: 94%
“…2A). No electron density was observed for SDS22 residues 56-75, consistent with previous data demonstrating that these residues are both dispensable for PP1 binding (22) and less well ordered than the Leu-rich repeats (LRRs) (36,37). The SDS22:PP1 interaction surface is extensive, burying more than 3084 Å 2 of solvent accessible surface area (Fig.…”
Section: Sds22 and Other Pp1 Regulatory Proteins Prevent Pp1 Aggregatsupporting
confidence: 87%
“…Consistent with these reports, our results indicated that BCLAF1 knockdown reduced cell proliferation and increased cell susceptible to IR-induced DNA damages in GC cells. Recent studies indicated that BCLAF1 function mainly depends on its phosphorylation, for example, Ewald Heroes et al reported that the BCLAF1:SDS22 interaction is dependent on the phosphorylation of BCLAF1 [29]. By searching the uniport protein database, 46 phosphorylation sites were found in BCLAF1, but the signi cance and function of these sites have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from LRR-containing genes from human pathogen Leptospira interrogans such as LIC11098 that exhibits a high structural similarity with Zscores of 26.6 (root-mean-square-deviation, RMSD, of 2.0 Å) (24), it is noteworthy that the structure of Rsu-1 resembles that of a human protein phosphatase 1 regulatory subunit 7 (a.k.a. SDS22) (25), a prototype of SDS22-like subfamily in the LRR superfamily (10) (Figure S1). Rsu-1 shares a 27% sequence identity with SDS22 that comprises 12 LRRs (25).…”
mentioning
confidence: 99%
“…SDS22) (25), a prototype of SDS22-like subfamily in the LRR superfamily (10) (Figure S1). Rsu-1 shares a 27% sequence identity with SDS22 that comprises 12 LRRs (25). The structure of Rsu-1 superimposes with that of SDS22 with an RMSD of 2.8 Å for the equivalent C atom pairs.…”
mentioning
confidence: 99%